THE INFLUENCE OF THE MANAGER ON ORGANIZATIONAL HEALTH - Silva, Patric; Costa, Elvio (Revista Interface Tecnológica, 2023)
Contemporary organizations are increasingly attentive to creating and encouraging quality of life at work programs, as they recognize that an employee who works in a harmonious and safe environment produces more and brings satisfaction to the organization, minimizing stress. This article aims to identify and contextualize the challenges and preparation of managers in the face of organizational health. And the specific objectives were: 1) to raise perceptions regarding the manager's influence on the organizational health of employees and 2) to diagnose the main causes of employee demotivation. The methodology used was a bibliographical survey in the most relevant database of scientific works already carried out and the application of a case study in two companies in the city of Araraquara, and as an instrument of data collection a questionnaire carried out at 5 managers and 17 employees of the companies in question, in order to identify positive and negative points in relation to the subject addressed. The results indicate that managers influence the productivity of employees, mainly with regard to the impartiality of the manager, and especially in the good relationship between team members and co-workers. On the other hand, negatively, it is perceived that excessive demands, psychological pressures, lack of encouragement and recognition can harm the health and performance of employees.
Keywords: People management; Organizational Healt; Organizational Climate; Quality Life at Work; Manager Influence